Captain America : man out of time. Part 2 - Waid, Mark, 1962- (Spotlight, 2012)
"The Avengers Iron Man, Thor, Giant Man, and Ant-Girl have pulled a mysterious, tattered soldier from the sea. What they don't know is they brought back to life the Living Legend of World War II. He's a man whose memories of a life 60 years ago are as fresh as yesterday! How will Steve Rogers, frozen in suspended animation for more than 50 years, adapt to the world of the 21st century?"--P. [4] of cover.